The Importance of Utilizing Metaphors and Similes in News Media - Srour, Sana Issa; Murad, Ali Hama (د محمد أمين الضناوي, 2022)
ترتبط صناعة الأخبار والوسائل الإعلامية على وجه الخصوص بوسائل الإعلام إذ تستهدف الأخبار الجمهور، فيكون تحت مجهر الأخبار هناك أنواع من وسائل الإعلام مثل وسائل الإعلام المطبوعة التي تشمل الصحف والمجلات الإخبارية والأخبار المتلفزة أو المذاعة كما هو الحال في الراديو والتلفزيون، وهنالك أيضا النوع الذي يتعلق بالوسائط التكنولوجية، أو الرقمية وهو الإنترنت. يتضمن هذا النوع نسخة رقمية من الوسائط الأتية: الصحف عبر الإنترنت والمدونات الإخبارية ومقاطع الفيديو الإخبارية والبودكاست الإخباري والأخبار الحية. تندرج وسائل الإعلام الإخبارية ضمن وسائل الإعلام التي تؤثر على خصوصية القراء من حيث مصادر الأخبار. يحدث هذا التأثير من خلال اللغة، ومن خلال تأثير العديد من العناصر الأخرى. فإذا، يمكن للمؤلفين الإعلان عن أعمالهم الإبداعية، وكذلك أعمالهم المبتكرة وتسويقها، من خلال استخدام اللغة. ومع ذلك، ما يزال هذا الأمر غير مكتمل من دون الاستخدام والتوظيف المناسبين للأدوات التصويرية، أو استعمال التشابيه في الكلام. الغرض من الدراسة هو الكشف عن فعالية استخدام الاستعارات والتشبيهات كأدوات للتأليف في وسائل الإعلام الإخبارية. تتبين نتائج الدراسة من خلال نتائج استخدام الاستبيان ثنائي التفرع من النوع نعم -لا وتشير الإجابات بنعم على الأسئلة المحددة إلى المصداقية، والموثوقية، وتنقل نتائج مهمة: نسبة عالية تبلغ 79% من الإجابات بنعم، و21% من الإجابات بنعم، من قبل المشاركين في الدراسة. News industry and news media in particular are related to mass media where the news targets the public, and the public is under the lens of the news. There are types of mass media such as the print media which includes newspapers and news magazines, the televised or broadcast news as in radio and television, and the last type is related to technological or digital media which is the Internet. This type includes a digitized version of the following media: online newspapers, news blogs, news videos, news podcasts, and live news. News Media come under Mass Media which influence the readers’ exclusiveness in terms of the sources of news. This influence takes place through language, among many other elements. Through using language, authors can advertise and market their creative as well as their innovative works. However, this is still unaccomplished without the adequate usage and employment of figurative devices or figures of speech. On the one hand, an example is a metaphor which functions as an embedded comparison between two different things, aspects or ideas such as the use of the expression “heart of stone” or Shakespeare’s “the world is a stage”. On the other hand, a simile is a comparison between two things which are not alike, through using the words “like” or “as”. An example is the expression ‘she is like the moon’. The purpose of the study is to reveal the effectiveness of using metaphors and similes as authorship tools in news media. The findings of the study are indicated by the results of the dichotomous questionnaire of yes-no type. The yes-answers on the given questions are indicative of authenticity, reliability, and convey significant results: a high ratio of 79% Yes-answers and 21% No-answers, by the study participants/respondents.
Keywords: وسائل الإعلام -- البلاغة اللغوية -- الإعلام الإخباري